Ascorbic acid is a dose-dependent inhibitor of adipocyte differentiation, probably by reducing cAMP pool - Rahman, Fryad; Al Frouh, Fadi; Bordignon, Benoit; Fraterno, Marc; Landrier, Jean-François; Peiretti, Franck; Fontes, Michel (Frontiers in Cell and Developmental Biology, 2014)
Ascorbic acid (AA) has been considered, for a long time, only as the active principle of vitamin C, with antioxidant properties. We recently demonstrated that ascorbic acid is a competitive inhibitor of adenylate cyclases, acting as a global regulator of cAMP pool. It was thus interesting to determine new targets of AA, linked to its potential signalling capacity, especially during cell differentiation. We demonstrated here that AA is an inhibitor of preadipocyte cell lines differentiation. This inhibition is dosage dependent. In addition, we describe the impact of AA on expression of genes involved in adipogenesis and/or adipocyte phenotype. Moreover, our data suggest that AA treatment partially revert lipids accumulation in mature adipocyte. These properties are probably linked to the function of AA as a global regulator of the cAMP pool, as an analogue of AA, without antioxidant properties, has the same effect. In addition, we demonstrated that AA inhibits adipogenesis in a mesenchyme cell line, OP9, but drived differentiation of this line toward osteogenesis. Finally, our data suggest that the intracellular transporter SVCT2 is involved in these process and could act as a receptor.